Medical treatment of acquired uterine arteriovenous fistulae related to pregnancy: 2 case reports and literature review - Huang, Lingna; Qiu, Lini; Zhang, Jinwen; Ye, Hui; Xiong, Xiumei (Frontiers in Medicine, 2025)
Uterine arteriovenous fistula (UAVF) is a rare form of uterine arteriovenous malformation, the most characteristic clinical symptom of which is intermittent vaginal bleeding. Currently, reports on the treatment of UAVF mainly focus on uterine artery embolization (UAE), high-intensity focused ultrasound (HIFU), and surgical treatment, with relatively few reports on medical conservative therapy. This article reports the process and outcomes of medical treatment for two cases of pregnancy-related acquired UAVF and summarizes and analyzes the indications and drug selection for UAVF medical conservative treatment based on the relevant literature.